Pengaruh Problem Based Learning Terhadap Hasil Belajar Matematika Kelas V SDN Kota Bengkulu - Ikhsan, Fakhrurrozi; Agusdianita, Neza (JURIDIKDAS, 2024)
The reason for this review is to decide the impact  of PBL on mathematics learning output in class V at SDN Gugus XII Bengkulu City. This exploration is a quantitative examination, with a Semi Trial research strategy with the exploration plan The Matching Just Pretest-Posttets Control Gathering Plan. The populace in this examination is  Class V SDN Gugus XII Bengkulu City consisting of SDN 81, 99, 20 and 60 which are in Bengkulu City. The example in this review is the control class will be classV SDN 99 Bengkulu City and the trial class will be class V SDN 81 Bengkulu City. Sampling using cluster random sampling. The review tool includes multiple choice questions test through the pretest given before active research and posttests are given after active research activities. Information studies are studied using descriptive analysis, reflection tests, and inferential analysi. The pretest t test of the experimental class and the control class obtained t count 0.457 <t table 1.672, then the experimental class and control class had the same initial abilities, and the results of the posttest t test data, tcount value 3.085 > ttable value 1.672. So it was presumed that there was an impact of the use of the PBL learning model on mathematics learning outcomes in class V at SDN Gugus XII Bengkulu City. since there were various medicines for the control class and exploratory class.